Graphene nanobuds: Synthesis and selective organic derivatisation. (December 2016) - Georgakilas, Vasilios; Bourlinos, Athanasios B.; Ntararas, Evangelos; Ibraliu, Armando; Gournis, Dimitrios; Dimos, Konstantinos; Kouloumpis, Antonios; Zboril, Radek
Abstract: Herein, the formation and selective organic derivatisation of graphene nanobud, an all carbon nanohybrid comprised by C60 and graphene, are presented. C60 cages are directly attached to the graphenic surface with stable covalent bonds. Importantly, prepared graphene nanobud shows remarkable dispersibility, decreased number of defects and highly aromatic character that are associated to improved electrical conductivity compared to pristine graphene. The high chemical reactivity of the curved sp 2 carbon atoms of C60 led to a selective covalent attachment of organic groups onto C60 avoiding damage of the graphene aromatic system.